Integrated Information System Teaching Plan in College Using FAST Method and Twitter Bootstrap - Ika Ratna Indra Astutik; Mochamad Alfan Rosid (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
AbstractTeaching plan is one of the obligations that must be made by lecturer before conducting any lecture because teaching plan will be used by lecturer as a reference in determining Learning Outcomes (LO) and providing recovery materials in each semester. Unfortunately, there are still many existing teaching plans in College which are still manually developed. Thus, they may undermine head courses and Institute of Educational Development Study and Majors to perform learning monitoring and evaluation in the department.This research developes a system application which facilitates lecturer in managing teaching plan recovery and facilitates the Institute of Educational Development Study and Majors in evaluating the learning effectiveness, the suitability of the teaching journal and the achievement of Learning Outcomes. The system is developed using FAST method (Framework for the Application of System Thinking) and designed using a responsive Twitter Bootstrap template. The information generated system can also be used to support the cccreditation of Program Study. The testing process in this system uses blackbox testing to check the stability of the deployed system. The result of the test shows that all functions in the system runs perfectly, and the lecturers are more easily managing the Teaching plan, and the head of the Department can evaluate the suitability of the Teaching plan with teaching journal.